Penerapan Rendam Kaki Air Hangat Jahe Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi Di Kelurahan Joyotakan - Dwi Aria Susanti; Tri Susilowati; Muhammad Natsir (An-Najat, 2024)
Background: Hypertension is a major health problem in developed and developing countries, is a non-communicable disease and is one of the complications that causes the number one death in the world. Presentation of hypertension in Central Java In 2021, hypertension cases will be 37.57%. Based on gender, the prevalence of women is greater than men, namely 15,845. Hypertension sufferers in Surakarta with a percentage of 20.5%. One non-pharmacological therapy that can be done for hypertension sufferers is soaking their feet in warm ginger water. Soaking feet in warm ginger water is one of the complementary therapies currently used to reduce hypertension. Objective: To determine the results of applying warm ginger water foot soak therapy to reduce blood pressure in hypertension sufferers in Joyotakan Village. Method: Using a descriptive method with a case study design approach, respondents used 2 hypertensive patients, determining respondents based on inclusion and exclusion criteria was carried out 4 times in 1 week. Soak your feet in warm ginger water and measure your blood pressure using a sphygmomanometer. Results: Giving a warm ginger water foot soak was able to reduce blood pressure in 2 respondents after being given a warm ginger water foot soak 4 times in 1 week in Joyotakan Village. Conclusion: There were changes in 2 respondents after soaking their feet in warm ginger water 4 times in 1 week in Joyotakan Village.